ANALYSIS OF PRODUCT QUALITY BOGIE SET S2HD9C USING SIX SIGMA AND FMEA METHOD AT PT. BARATA INDONESIA (PERSERO) - Ramadhani, Muthia Dita; Rochmoeljati, Rr. (Center for Study and Journal Management FTI UMI, 2024)
Product quality is critical for businesses to survive and thrive in the marketplace. Likewise with PT. Barata Indonesia (Persero), which always wants to provide good product quality for customer satisfaction, PT. Barata Indonesia (Persero) is a State-Owned Enterprise (BUMN) in the manufacturing sector, which has a business line in the foundry or foundry sector, one of which is the production of train components. The company's difficulty is that there are still problems in producing the S2HDC bogie set, such as break mold, porosity, slag, and crack. This study aimed to analyze the quality of the Bogie Set S2HD9C product using the six sigma method and propose improvements using Failure Mode and Effect Analysis (FMEA). The research results found that the percentage of defects that occurred during August 2022 - January 2023 was porosity of 40.38%, break mold of 30.77%, crack of 17.31%, and slag of 11.54%. To obtain an average DPMO of 14191 with a sigma value of 3.69. The causes of these defects are caused by human, material, machine, method, and environmental factors. From the FMEA analysis, the defect's cause is the highest RPN value of 392, with the proposed improvement to closely monitor the cleaning process and recheck the core box in every process that will use the mold.